The Spanish model of New Journalism in a European context. Issue 3 (1st September 2016) - Eiroa, Matilde; Sánchez-Illán, Juan Carlos; Sanmartí, Josep M.
Abstract: This work deals with the study of the evolution and the historical experience of Spanish journalism in the context of decades of transition between the nineteenth and twentieth centuries. From the selection of the most relevant cases and the examination of tracking, or not, of models and European patterns of the reference press, singularities and analogies of the historical evolution of the Spanish journalism model may be seen – an evolutionary model fully registered within the framework of Western Europe and in one of its most fruitful phases: the origins and first development of the mass media. Therefore, the following trilogy of reference media is selected covering specified time periods: El Imparcial, Madrid, 1867–1933; La Vanguardia, Barcelona, 1881; and ABC, Madrid, 1903.